LEARNING THROUGH INTERACTIVE MEDIA IN IMPROVING ELEMENTARY SCHOOL STUDENTS' LEARNING MOTIVATION - Intan Permata Sari (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
ABSTRACT This research method uses a qualitative descriptive method that explains the phenomena that occur in the world of education, especially elementary schools. This study aims to provide information about interactive learning through PowerPoint media accompanied by other media. Through this research, students can increase their learning motivation. Learning at the elementary school level is foundational and crucial for a child's holistic development. This stage sets the groundwork for lifelong learning, social skills, emotional growth, and intellectual capabilities. Building an Academic Foundation is an obligation for the state to pay more attention to the field of education and the progress of a country. Students are taught to read, write, and do basic arithmetic, essential skills for future education and everyday life. Students are taught about the introduction of problem solving and reasoning preparing children to face challenges logically. Subjects such as science, social studies, and art expand understanding of the world. Primary education is the foundation for a child’s development, shaping not only their academic success but also their personal and social development. By providing a supportive, engaging and encouraging environment, primary schools equip children with the tools and confidence they need to thrive in the future. Investing in quality education at this level has a lifelong impact on individuals and society as a whole.